Hubungan Umur Penyapihan Dan Pola Asuh Makan Terhadap Status Gizi Anak Balita Usia 25-36 Bulan Di Desa Purwosari Kabupaten Wonogiri - Dwi Hastuti, Rahayu; , Muwakhidah, SKM., M.Kes; , Dyah Widowati, SKM (2016)
Introduction : Indonesia is still experiencing various nutritional problems include malnutrition in children under five. Factors that can prevent nutritional problems on children under five include weaning age and eating care pattern. Breastfeeding until appropriate weaning age and applying good eating care pattern will affect the nutritional status of children under five. Objective: To determine the relationship between weaning age and eating care pattern with the nutritional status of children aged 25-36 months at Purwosari Village, Wonogiri Regency. Method : This study was observational research with cross-sectional design. The samples were 40 and selected through multistage random sampling technique. Data of weaning age and eating care pattern were obtained through interviews using questionnaire. Data of nutritional status was obtained by anthropometric measurements. Statistical analysis using Spearman rank correlation statistical tests. Result : Most of children aged 25-36 months of Purwosari Village Wonogiri Regency ( 85 %) had been weaned at the right weaning age ( 24 months ). Most of children had good eating care pattern (92,5 %). Children who had good enough eating care pattern were 7,5 % and children who had less good eating care pattern were 0 %. Most of children (90%) had normal nutritional status based on weight for height index. Children who had severely wasted nutritional status were 0%, wasted nutritional status were 5 %, and overweight nutritional status were 5 %. Conclusion : There was a relationship between weaning age and nutritional status of children aged 25-36 months at Purwosari Village, Wonogiri District (p=0,003). There was a relationship between eating care pattern and nutritional status of children aged 25-36 months at Purwosari Village, Wonogiri District (p= 0,000).